ASSESSMENT AND COMPARATIVE ANALYSIS OF THE INVESTMENT POTENTIAL OF THE REPUBLIC OF BELARUS AND THE REPUBLIC OF UZBEKISTAN WITHIN THE EAEU - Nigora Gulomova (Western European Studies, 2023)
This article delves into an examination of the investment climates of both the Republic of Belarus and the Republic of Uzbekistan within EAEU countries by providing a comparative analysis of factors like political stability, infrastructural development, regulatory frameworks, macroeconomic indicators and FDIs of these countries. It also provides insights into the trends and patterns of investment growth in these nations. The paper helps to understand the evolving investment narratives in the EAEU region and provides a roadmap for stakeholders looking to navigate the investment landscapes of Belarus and Uzbekistan.
Keywords: Investment; investment potential; inflow; outflow